Efektivitas Video Animasi dalam Meningkatkan Motivasi Menggosok Gigi pada Siswa SDN Gurah 1 Kabupaten Kediri - Wildan Arpandu; Endah Retnani Wismaningsih; Mohamad Anis Fahmi (Ficco Scientific Corner, 2024)
Background: Dental health problems, particularly dental caries, are common among children. In school-age children, dental diseases are a significant concern as they not only cause pain but can also lead to infections spreading to other parts of the body, ultimately reducing productivity. One effective educational tool to promote dental health is video media. Animated videos, which combine visual and auditory elements, can enhance curiosity, improve student engagement, and stimulate motivation. This study aims to analyze the effect of animated video on the motivation of students at SDN Gurah 1, Gurah, Kediri, to brush their teeth. Methods: This research employed a pre-experimental design with a one-group pre-test and post-test approach. A single group of students was assessed for their motivation to brush their teeth before and after the intervention. Data analysis was conducted using the non-parametric Marginal Homogeneity test. Results: The statistical analysis yielded a significance value of p = 0.000, indicating a significant difference in students' motivation before and after watching the animated video. Conclusions: The study concludes that the use of animated video significantly enhances students' motivation to brush their teeth. Implementing animated video as a learning medium in dental health education can be an effective strategy to improve oral hygiene habits among school children.